EKSPLORASI MEDIA 3D KULINER NUSANTARA UNTUK PENGUATAN ELEMEN MENGENAL DAN MENGHARGAI BUDAYA PADA PESERTA DIDIK DI SB AT-TANZIL MALAYSIA - Annisa Wahyu Kumalasari; Ridha Sarwono; Yogi Ageng Sri Legowo; Kholis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of using 3D interactive Student Worksheets (LKPD) with the theme of Indonesian culinary in strengthening the elements of recognizing and appreciating culture in students at SB At-Tanzil Malaysia. This type of research is quantitative descriptive with a one-group pretest-posttest design involving 10 elementary school students. Data were collected using a validated Likert-scale questionnaire and covered three main aspects, namely cognitive, affective, and psychomotor. The results showed an increase in the average score from 4.17 in the pretest to 4.55 in the posttest with an N-Gain value of 0.50 which is included in the moderate category. The normality test using Shapiro–Wilk showed that the data were normally distributed (p > 0.05), while the paired t-test showed a significant difference between before and after treatment (sig < 0.05). These results indicate that the use of 3D interactive LKPD is effective in improving students' understanding and appreciation of culture through physical activities such as cutting, folding, and sticking traditional culinary models. Theoretically, this research strengthens the concept of Ethnodigital Pedagogy in the form of non-digital manual media that can simultaneously integrate the cognitive, affective, and psychomotor domains. Practically, the results of this study can serve as an alternative contextual learning medium to foster Indonesian identity and cultural pride in foreign schools